Examination of the empirical dimensionality of job performance construct / Johanim Johari, Khulida Kirana Yahya and Abdullah Omar - Johari, Johanim; Yahya, Khulida Kirana; Omar, Abdullah (Research Management Institute (RMI), 2009)
This study attempts to examine the psychometric properties of the job performance constructs by espousing task performance and organizational citizenship behavior (OCB) items. The latter comprises of sportsmanship, civic virtue, courtesy, altruism, conscientiousness, and innovative behavior. A priori proposition was made that the job performance measurement could be explained by two factors, which are task performance and OCB. SPSS version 12 and AMOS 6 were used to analyze the data. Findings supported the hypothesis that job performance could be measured by the two hypothesized factors. However, four factors of OCB i.e. civic virtue, sportsmanship, conscientiousness, and courtesy, loaded on the task performance factor, while altruism and innovative behavior loaded on the OCB construct. Findings showed evidence of construct validity of the job performance items, indicating that the instrument can be used in the Malaysian studies.